BMP implementations in Himalayan context: can a locally-calibrated SWAT assessment direct efforts? - Ali, S.S.; Mehmood, H.; Chemin, Yann H. (2014)
Soil erosion due to accelerating runoff in various land cover types pose a serious threat to the long term sustainability of the fragile Himalayan landscape characterized by subsistence farming. Delimitation of high runoff zones, fostering soil erosion in the agricultural dominated watersheds is thus a necessity for watershed managers, NGO’s, urban planners, policy makers, and municipal administrations. The approach is practical, SWAT is a straightforward modeling system using GIS information. The BMP is also a very practical approach to mitigation of runoff accumulation on sub basin. A set of interviews with people familiar to the issues locally strengthened the confidence in the results. Results from this research show that terraces can reduce storm water runoff very effectively. There is a huge difference in amount of runoff after terraces are added to the simulation. Results showed a reduction of 57% in runoff volume during August 2004. If the area near the river is preserved as a buffer strip and a tree cover is maintained around it then it minimizes the effect surface runoff. The effect of riparian buffer is modeled in SWAT and the results show about 6% decrease in surface runoff when a buffer of 500 m is applied around the main river only. This study has drawn a location map of BMP implementations of most meaningful impact for the rehabilitation and safeguard of rivers, streams, lakes and wetlands around the river Siran in the Mansehra Tehsil, Pakistan.